WOOD PRODUCTS (CARTON) TREATMENT WITH LOW POWER DIODE LASER AND OPTIMIZATION OF PROCESSING PARAMETERS - Pacejs, Antons; Diduhs, Artūrs; Novikovs, Aleksandrs; Narica, Pāvels (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The Embalser is designed as and affordable entry-level laser cutter and engraver. Ideally suited to the hobbyist, artist and professional who is looking for a laser which is simple to use and without all the complexities of CO2 based system. The 4 watts of laser power (1/10th the power of a standard CO2 system), is more than capable of working with materials such as paper, leather and some plastis. Optimizing the parameters could succeed in improving finel result.